Interaction in professional discourse in job interviews / Isai Amutan Krishnan - Krishnan, Isai Amutan (2014)
The study focuses on an investigation into interaction in professional discourse in job interviews: Interpersonal Meanings in terms of Mood and Modality (Halliday, 1994), Impression Management (Steven & Kristof, 1995) and Communication Skills (Truman, 2011). A qualitative research design (Creswell, 2008 &Jackson, 2011)was used to elicit data involving content analysis of interview transcripts for the use of Mood and Modality features. Additionally, the interviewer‟s impression of the candidates in four aspects, namely, self-focus, self-presentation, exemplification and entitlements as well as communication skills namely completeness, conciseness, clarity and correctness were also analysed. Data were obtained from ten interviews. The findings showed that the Mood and Modality resources predominantly used by the interview candidates were the low modal finite „can‟ (n=24;29%) and the median modal finite „will‟ (n=28;34%). Less significantly used were the low modal finites which are „may‟ (n=2;2.4%), „could‟ (n=2;2.4%) and „might‟ (n=3;3.6 %,) and the median modal finite which is „should‟ (n=4; 4.8%) and the high modal finite which is „must‟ (n=2;2.4%). Other median modal finites which are „is to‟ and „was to‟ and other high modal finites which are ‟ought to‟, „need to‟, „has to‟ and „had to‟ were not used at all by the interviewees. Most of the interview candidates were not able to use the Mood and Modality resources successfully in the job interview as the candidates typically use the low modal finite „can‟ and the median modal finite „will‟ in everyday conversations. Therefore, they naturally used „can‟ and „will‟ in the job interviews although their use was at times not appropriate. This leads to candidates being unable to carry out a professional conversation in job interviews. Where Impression Management aspects are concerned, the interview candidates did very well in the „exemplification‟ (n=10;52.6 %) category. They did reasonably well in the, „entitlement‟ (n=10;50%) and „self-presentation‟ (n=11;40.7%) categories, which fall under the good category compared to „self-focused‟ (n=14;50%) which falls under the average category. Most of the interview candidates scored under the good not the excellent category. Only three candidates were rated excellent for Impression Management however they did not display the entitlement aspect at all. It may be concluded that none of the four Impression Management aspects were fully displayed by the interview candidates. The candidates were not able to impress the interviewers as they were not competent to answer the questions. Communication skills aspects are also concerned in the job interviews. The interview candidates were able to express reasonably well in the „completeness‟ (n=16;53.3%) aspectwhich falls under the excellent category and „correctness‟ (n=8;38%) element which falls under the good category.The candidates were not able to express „conciseness‟ (n=8;40%) and „clarity‟ (n=8;28.5%), which fall under the good categories. The candidates lacked Communication Skills in terms of clarity and conciseness. These two aspects are usually neglected but are important expects to carry out a good conversation in job interviews. The findings of the current study have shown that Malaysian graduates seeking employment need to develop on many fronts, namely, in convincing the interviewer with the required qualities and creating a positive impression in job interviews. Apart from that, the ability to articulate thoughts and listen to the questions and answer in an appropriate manner would create a positive image of job seekers.